Patent analysis as an approach to the conceptual design for whey syrup production (2017)
In this work, technological trends were identified for the production of sweetening syrup and the use of whey by means of a review of patents in the databases of Espacenet, Google Patent Search and the Superintendency of Industry and Commerce of Colombia (SIC). A total of 226 documents were found, out of those 119 are international patents, and 107 applications registered in the SIC. Only three documents deal with the production of sweetening syrup; the rest are mainly oriented to the extraction of the proteins contained in the whey and its application in different fields. It is concluded that there are currently technologies required for the production of whey sweetener syrup, and that the information obtained serves as a basis for the conceptual design of this process in the Colombian context. In the absence of a patent describing the whole process of producing whey syrup in conjunction with the obtaining of concentrates and protein isolates, an opportunity is opened to offer to the Colombian dairy sector a future technological package for the integral use of whey.